Agrarian reform in the Philippines democratic transitions and redistributive reform - Riedinger, Jeffrey M. (Stanford University Press, 1995)
This analysis of agrarian reform in the Philippines evaluates the capacity of new democratic regimes to promote redistributive agrarian reform, an issue of concern to developing countries throughout the world.